Awareness and perceptions of Filipino obstetrician-gynecologists on fertility preservation: a cross-sectional survey - Glaiza S. de Guzman; Eileen M. Manalo; Maria Jesusa B. Banal-Silao (BMC, 2023)
Abstract Background The demand for fertility preservation has increased substantially over the past decade as more women wish to delay childbearing and with improved survival outcomes of various medical conditions. This study evaluated the awareness and perceptions of Filipino obstetrician-gynecologists on fertility preservation. Methods A cross-sectional survey was conducted among diplomates and fellows of the Philippine Obstetrical and Gynecological Society from September to December 2021. A self-administered questionnaire with 24 items was distributed online. Univariate descriptive statistics were reported as means for continuous variables and frequencies with percentage for categorical variables. Differences in responses were tested using the chi-square test. Results A total of 215 respondents completed the survey. Majority of the respondents were female, general obstetrician-gynecologists practicing in the National Capital Region. There was an overall positive perception of fertility preservation, with 98.60% agreeing that discussions about childbearing intentions should be initiated. Most participants (98.60%) were aware of fertility preservation but had varying levels of awareness of the different techniques. Fifty-nine percent of the respondents were unaware of regulations on fertility preservation. Setting up dedicated centers for fertility preservation and offering it as a public service were viewed as necessary by the respondents. Conclusions This study underscored the need to increase awareness of fertility preservation techniques among Filipino obstetrician-gynecologists. Meeting the need for comprehensive guidelines and centers is essential to promote fertility preservation in the country. Efficient referral systems and multidisciplinary approaches should be established for holistic care.